Can rules of origin in sub-Saharan Africa be harmonised? A political economy exploration - Peter Draper; Heinrich Krogman; Cynthia Chikura (Deutsches Institut für Entwicklungspolitik (DIE), 2016)
The number of preferential trade agreements has increased sharply over the past decade as a response to stagnant multilateral trade negotiations. Political economy features centrally in these negotiations, for instance in the context of the Continental Free Trade Agreement (CFTA), which resulted from the most extensive negotiations for a preferential trade agreement ever to take place in Africa. In this paper, we discuss the challenges of rule-oforigin harmonisation in this process, which is a critical element for any further integration initiative in the continent. In particular, we review different approaches to the formulation of rules of origin, determining which firms qualify to take advantage of negotiated concessions. We focus on the experiences of the three African regional economic communities (COMESA, EAC and SADC) that are busy merging into the Tripartite Free Trade Agreement (TFTA) and assess their potential for harmonisation, drawing also on the examples of similar efforts being made around the globe, such as for the Trans-Pacific Partnership (TPP) and the Transatlantic Trade and Investment Partnership (TTIP). Strict rules of origin – as implemented by the European Union and the United States – require strong state institutional capacities to implement them and for competitive firms to incur high compliance costs. These two conditions are absent in most African countries. We hence caution against adopting rules of origin for the South African model in the CFTA on the basis of their restrictive nature and the high level of institutional and organisational capacities required for implementing them. Furthermore, we argue that rigid approaches risk undermining the very objectives they seek to achieve, since – for the most part – Africa's private sectors are comprised of small and informal enterprises that are illequipped to take advantage of rigorous rules of origin.
Keywords: 330; Handel und Investitionen; Regional + global + transnational governance